MEMBONGKAR MISTERI DNA- RNA DALAM PERSPEKTIF EPISTEMOLOGI DAN ONTOLOGI MONISTIK - TEOLOGI ATMA TATTVA - Made Aripta Wibawa (Sanjiwani: Jurnal Filsafat, 2018)
Cell is a smallest unit in life. In Biology theory, bacteria and protozoa are organisme have one only cell. Every one kilogram weight has one trilliun cells, it means who one has 60 kg weight has 60 trilliun cells. A baby who has 3 kg weight has 3 trilliun cells. Every human beings (tree, animal and human) has onle one cell recourcess. Action, thought and imagination activities is one cell acted. The four main component as chemical structure: H, O. N and C. Its means, cell is composesd by many kinds of chemical anorganic. The question is : Is DNA and RNA is so formed that DNA and RNA is formed as the body material component to be life as todays?